Republic Act 11032 Policy Implementation and Customer Satisfaction in Calamba Water District: Basis for Action Plan - Quiatchon, Joseph Bernard (Journal of Interdisciplinary Perspectives, 2024)
This research investigated the relationship between the implementation of Republic Act 11032 and customer satisfaction within the Calamba Water District (CWD) in Laguna province. The study aimed to identify the factors influencing CWD’s ability to achieve optimal customer satisfaction by the Act's regulations by examining challenges, concerns, and potential obstacles. Employing a descriptive-correlational quantitative research design, the study surveyed 428 respondents, including 61 Commercial Department personnel and 367 concessionaires, who were randomly sampled. Data collection was conducted using an adapted research instrument. The findings indicate a significant relationship between the level of Republic Act 11032 policy implementation and customer satisfaction in CWD. The probability values of .000, .012, .000, .001, .000, .000, .000, .000, .000, .000, .000, .000, and .000 were less than the level of significance at .05, thus the null hypothesis was rejected. However, this relationship was not significant in areas such as Citizen’s Charter Provisions and Basic Facilities, Government Access through Frontline Services and Basic Facilities, and Zero Contact Policy and Basic Facilities. The probability values of .449, .849, and .855 were greater than the level of significance at .05, this accepting the null hypothesis. Based on these findings, the study proposes an action plan aimed at enhancing current implementation strategies and introducing innovative approaches. This plan focuses on improving communication between the District and its stakeholders, investing in better facilities, and enhancing the skills of frontline employees to boost productivity and customer confidence. Consequently, the research contributes to the development of effective strategies for policy implementation in public service organizations, promoting a culture of transparency and accountability.